Assessment of Haloferax mediterranei Genome in Search of Copper-Molecular Machinery With Potential Applications for Bioremediation - Llorca, Marina García; Martínez-Espinosa, Rosa María (Frontiers in Microbiology, 2022)
Heavy metals are essential micronutrients at low concentrations, serving as cofactors for relevant microbial enzymes (i.e., respiratory nitrate and nitrite reductases NADH dehydrogenase-2, amine oxidase, etc.), but they become harmful cellular intoxicants at significant low concentrations compared to other chemical compounds. The increasing need to incorporate bioremediation in the removal of heavy metals and other contaminants from wastewaters has led extremophiles to the spotlight of research. The haloarchaeon Haloferax mediterranei has promising physiological characteristics regarding bioremediation. However, little is known about how haloarchaea manage to resist high concentrations of heavy metals in the environment. The aim of this work is to develop bioinformatics research as the first step for further omics-based studies to shed light on copper metabolism in haloarchaea by analyzing Hfx. mediterranei genome (strain ATCC 33500). To reach this aim, genome and protein databases have been consulted, and copper-related genes have been identified. BLAST analysis has been carried out to find similarities between copper resistance genes described from other microorganisms and Hfx. mediterranei genes. Plausible copper importer genes, genes coding for siderophores, and copper exporters belonging to P1B-type ATPase group have been found apart from genes codifying for copper chaperones, metal-responsive transcriptional regulators, and several proteins belonging to the cupredoxin superfamily: nitrite reductase, nitrous oxide reductases, cytochrome c oxidases, multicopper oxidases, and small blue copper proteins from the amicyanin/pseudoazurin families as halocyanins. As the presence of heavy metals causes oxidative stress, genes coding for proteins involved in antioxidant mechanisms have been also explored: thioredoxin, glutaredoxin, peroxiredoxin, catalase, and γ-glutamylcysteine as an analogue of glutathione. Bioinformatic-based analysis of Hfx. mediterranei genome has revealed a set of genes involved in copper metabolism that could be of interest for bioremediation purposes. The analysis of genes involved in antioxidative mechanisms against heavy metals makes it possible to infer the capability of Hfx. mediterranei to synthesize inorganic polyphosphate granules against oxidative stress.